In vitro synthesis and integration into mitochondria of porin, a major protein of the outer mitochondrial membrane of Saccharomyces cerevisiae. - Mihara, K (1982)
We have isolated an outer mitochondrial membrane (OMM) fraction from baker's yeast. Saccharomyces cerevisiae, that possesses porin activity and contains a major polypeptide of 29,000 daltons. By analogy to similar data for an OMM fraction from rat liver and mung bean [Zalman, L. S., Nikaido, N. & Kagawa, Y. (1980) J. Biol. Chem. 255, 1771-1774], the 29,000-dalton polypeptide of the isolated yeast OMM fraction has been tentatively identified as porin. Evidence to substantiate this identification was provided by the finding that both the porin activity and the 29,000-dalton polypeptide were entirely resistant when the OMM fraction was exposed to trypsin digestion, with the 29,000-dalton polypeptide being virtually the only polypeptide in the OMM fraction to be unaffected by trypsin digestion. There was no protection when trypsin digestion was carried out in the presence of detergent. Using monospecific antibodies, we have shown that yeast porin is apparently not synthesized as a larger precursor in a cell-free translation system. In vitro-synthesized porin could not be integrated into dog pancreas microsomal vesicles or into an isolated OMM fraction from yeast, either co- or posttranslationally. In vitro-synthesized porin, however, could be integrated posttranslationally into whole isolated mitochondria. This membrane specificity suggests that integration does not proceed by unassisted partitioning. The integration of porin into whole mitochondria occurred with fidelity by the criterion of its resistance to trypsin. Moreover, integration was not inhibited in the presence of the protonophore carbonyl cyanide m-chlorophenyl-hydrazone whereas translocation into the mitochondrial matrix of the in vitro-synthesized gamma subunit of F1-ATPase was inhibited.